(3eHGOF GdQjGVI GdeGdjIs - (3CMeO YHO Gddg(B, (3OQhjTs ((3YeGf(B:s (3OGQ UaGA ddfTQ hGdJhRjY(B,s, 1997)
(3GdaGFOI hJWhQgG hehba GdTQGFY GdSeGhjI efgG, GdaGFOI GdHSjWI hJWHjbGJgG, SOGO GdOjhf bUjQI JCLd, NUe GdOjhf bUjQI GdCLd, JShjI GdOjhf hGSJHOGdgG, GdaGFOI GdeQcHI, GdeYOd GdMbjbj GdeYOd GdCSej ddaGFOI, GdbjeI GdMGdjI, NUe GdOjhf GdWhjdI GdCLd, GSJgdGc GdbQRV GdWhjdI GdCLd, GSJgdGc GdCUhd GdKGHKI, JYOjd GdOjhf GdWhjdI GdCLd hGSJHOGdgG, YVh Jchjf GdCehGd, LOGhd GdaGFOI, GdSfOGJs
(3GdeQGLY U(B.236s
Keywords: (3GdeMGSHI GdJMdjdjIs